2018
DOI: 10.1007/s00204-018-2185-0
|View full text |Cite
|
Sign up to set email alerts
|

Membrane microdomains regulate NLRP10- and NLRP12-dependent signalling in A549 cells challenged with cigarette smoke extract

Abstract: Chronic obstructive pulmonary disease (COPD) is predicted to become the third leading cause of death and disability worldwide by 2030; with cigarette smoking (active or passive) being one of the chief cause of its occurrence. Cigarette smoke exposure has been found to result in excessive inflammation and tissue injury, which might lead to COPD, although the exact pathophysiology of the disease remains elusive. While previous studies have demonstrated the role of membrane-bound Toll-like receptors (TLRs) in cig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Lipid rafts are cholesterol-rich membrane microdomains well known to act as harbors for signaling molecules. They demonstrated the recruitment of proteins from the NLRP family in lipid rafts as well as their interaction with caveolin-1 [56]. Altogether, these data may suggest that upon PX exposure an inflammasome dependent pro-inflammatory response is initiated, which in turn induces the internalization of TJ proteins via caveolae.…”
Section: Discussionmentioning
confidence: 83%
“…Lipid rafts are cholesterol-rich membrane microdomains well known to act as harbors for signaling molecules. They demonstrated the recruitment of proteins from the NLRP family in lipid rafts as well as their interaction with caveolin-1 [56]. Altogether, these data may suggest that upon PX exposure an inflammasome dependent pro-inflammatory response is initiated, which in turn induces the internalization of TJ proteins via caveolae.…”
Section: Discussionmentioning
confidence: 83%
“…The correlations between these genes and smoking have also been reported. Compared with smokers, the expression level of CAV1 [ 56 ] and TOP2A [ 57 ] in non-smokers was reported to be lower, while the expression levels of TGFBR2 [ 58 ] and CAT [ 59 ] were reported to be higher in non-smokers. Taken together, although these hub genes all played essential parts in the evolution and progression of LUAD, the specific mechanisms remain not clarified, and future experimental analyses are still demanded.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (27) found that cigarette smoke-induced inflammasome activation was triggered by oxidative stress injury and Ca 2+ influx in human bronchial and alveolar epithelial cells. Besides the activation of NLRP3 inflammasome, Singh et al (31) observed that increase of NLRP10 and NLRP12 proteins in human alveolar type II epithelial cells challenged by cigarette smoke extract. Furthermore, Kaur et al (32) proved that NLRP10 knockdown rescued cigarette smoke extract induced inflammatory responses in human alveolar type II epithelial cells, which might serve as an effective therapeutic target of COPD.…”
Section: Stable Chronic Obstructive Pulmonary Disease (Copd)mentioning
confidence: 99%
“…Futhermore, Ji et al (24) pointed out that Shufeng Jiedu Capsule (SFJDC) and oseltamivir significantly decreased NLRP3 inflammasome activation in influenza virus A-induced AECOPD disease models. Targeting NLRP10 and NLRP12 inflammasome, polyunsaturated fatty acids (PUFA) was capable of rescuing A549 cells from cigarette smoke extract (CSE)-mediated membrane recruitment of NLRP10 and NLRP12, and also from inflammatory responses (31). Finally, Supplemental Figure 1 summarized effects of cigarette smoke on NLRP3 inflammasome, and potential therapeutic strategies.…”
Section: Therapeutic Strategies To Target Inflammasome In Cigarette Smoke-related Diseases and Physiopathological Disordersmentioning
confidence: 99%
See 1 more Smart Citation